Effect of Mesenchymal Stem Cells Overexpressing BMP-9 Primed with Hypoxia on BMP Targets, Osteoblast Differentiation and Bone Repair - Paz, Jessica Emanuella Rocha Moura; Adolpho, Leticia Faustino; Ramos, Jaqueline Isadora Reis; Bighetti-Trevisan, Rayana Longo; Calixto, Robson Diego; Oliveira, Fabiola Singaretti; Almeida, Adriana Luisa Gonçalves; Beloti, Marcio Mateus; Rosa, Adalberto Luiz (Biology (Basel, Switzerland), 2023)
Bone formation is driven by many signaling molecules including bone morphogenetic protein 9 (BMP-9) and hypoxia-inducible factor 1-alpha (HIF-1α). We demonstrated that cell therapy using mesenchymal stem cells (MSCs) overexpressing BMP-9 (MSCs+BMP-9) enhances bone formation in calvarial defects. Here, the effect of hypoxia on BMP components and targets of MSCs+BMP-9 and of these hypoxia-primed cells on osteoblast differentiation and bone repair was evaluated. Hypoxia was induced with cobalt chloride (CoCl2) in MSCs+BMP-9, and the expression of BMP components and targets was evaluated. The paracrine effects of hypoxia-primed MSCs+BMP-9 on cell viability and migration and osteoblast differentiation were evaluated using conditioned medium. The bone formation induced by hypoxia-primed MSCs+BMP-9 directly injected into rat calvarial defects was also evaluated. The results demonstrated that hypoxia regulated BMP components and targets without affecting BMP-9 amount and that the conditioned medium generated under hypoxia favored cell migration and osteoblast differentiation. Hypoxia-primed MSCs+BMP-9 did not increase bone repair compared with control MSCs+BMP-9. Thus, despite the lack of effect of hypoxia on bone formation, the enhancement of cell migration and osteoblast differentiation opens windows for further investigations on approaches to modulate the BMP-9-HIF-1α circuit in the context of cell-based therapies to induce bone regeneration.